Financial autarchy as contagion prevention : the case of colombian pension funds (2014)
Regulations restricting investment by pension funds in high-risk and foreign assets may quarantine member accounts from contagious transmissions during financial crises. We analyze contagion from U.S. equity markets to emerging market autarchic assets (Colombian private pension funds) during the recent financial crises. We test for volatility contagion between financial asset returns using a multivariate GARCH (M-GARCH) framework, where the S&P 500 is the source of contagion to the autarchic asset. We find no evidence of volatility contagion during the 2007-9 crises, indicating protection due to regulated portfolio restrictions. However, there is evidence of contagion during the recent sovereign debt crisis.